Identifikasi Penyakit Antraks Pada Sampel Darah Hewan Ruminansia Di UPT Laboratorium Kesehatan Hewan Dinas Peternakan Provinsi Jawa Timur Di Tuban - Setyawan, Sandi; Rahmawati, Annisa (Jurnal Pertanian Terpadu, 2025)
The rising need for animal-derived protein has contributed to the extensive rearing of ruminant animals such as goats (Capra aegagrus hircus) and cattle (Bos spp.) across Indonesia. East Java Province is among the key regions that supply livestock products including meat, eggs, and various other animal-based commodities. However, with the growth of ruminant livestock farming comes an increased risk of infectious diseases, including anthrax. Anthrax is an illness caused by Bacillus anthracis, a zoonotic pathogen capable of infecting both domestic and wild animals especially herbivores like cattle, sheep, goats, and some bird species-and it can also pose a threat to humans. Hence, consistent efforts in disease prevention and control are vital to safeguard livestock from such infections. This research was conducted to assess whether anthrax infection was present in ruminant blood samples analyzed at the Veterinary Health Laboratory Unit (UPT) of the East Java Provincial Livestock Service located in Tuban, utilizing the blood smear testing method. Laboratory examination of ruminant blood samples submitted to the UPT Veterinary Health Laboratory in Tuban during November 2024 indicated that all samples tested negative for anthrax Keywords: Ruminants, Anthrax, Blood Smear Test